"Less time committed to care": Beliefs About Electronic Visit Verification Among Adults Using Home-Based Personal Assistance Services. (March 2022) - Sage, Rayna; Mashinchi, Genna M.; Lissau, Ari; Standley, Krys; Ender, Justice
Abstract : In 2016, the federal government mandated that all Medicaid-funded personal assistance services be documented through an Electronic Visit Verification (EVV) program by January 2020. Most states have asked for extensions due to difficulties in implementation and strong opposition from consumer advocacy groups. Qualitative research has documented various concerns of consumers and consumer advocates. In 2020 (prepandemic), we conducted a mail survey of consumers which included questions regarding familiarity with, and attitudes toward, EVV. Respondents could also write in qualitative comments. This paper explores consumers' perceptions of EVV using four survey items related to fraud, benefits, concerns, and protection and 25 qualitative comments related to these topics. We found that respondents agreed most with statements focused on both concerns with EVV interfering with their care and help in reducing fraud. In general, the most common quantitative response to the statements was indifference. Qualitative comments centered on concerns about EVV interfering with services in a variety of ways, although there were also comments related to EVV being protective, beneficial, or helpful in reducing fraud. We also identified a new category in the qualitative comments about consumers' beliefs that the work done by their personal assistance service workers is underrecognized. We recommend that policy makers and service organizations continue to collect information from consumers as EVV is implemented and altered to both meet the expectations of the legislation and the needs of consumers and workers.